Case Report: Inflamed Jacobson nerve: an uncommon cause of persisting otalgia after an acute otitis media - Camurdan, Aybige; Kilgue, Alexander; Scholtz, Lars Uwe; Todt, Ingo (Frontiers in Surgery, 2024)
Introduction Otalgia can have multiple causes. Mostly otalgia is caused by a tubal dysfunction or an acute middle ear infection. This case describes a patient with an inflammation of the Jacobson`s nerve causing severe persistent otalgia after an acute otitis media. The patients complaints completely disappeared after neurolysis of the Jacobson`s nerve. Case presentation We describe a case of a 21-year-old female caucasian patient with acute otitis media and persistent intractable otalgia. Infection was first successfully controlled by antibiotics. But the patient reported a persistent otalgia not responding to analgetics. We performed a CT scan, which exhibited a regular aerated middle ear finding, and a diagnostic tympanoscopy to examine the middle ear structures particularly the tympanic Jacobson`s nerve as a possible cause for persistent pain. The following neurolysis of Jacobson`s nerve under general anaesthesia led to a resolution of otalgia. Conclusion An inflamed tympanic Jacobson`s nerve is a rare observation and a persisting otalgia after an acute otitis media not responding to conservative treatment can be treated by a neurolysis.